2018
DOI: 10.1074/jbc.ra117.000333
|View full text |Cite
|
Sign up to set email alerts
|

The MAZ transcription factor is a downstream target of the oncoprotein Cyr61/CCN1 and promotes pancreatic cancer cell invasion via CRAF–ERK signaling

Abstract: Myc-associated zinc-finger protein (MAZ)is a transcription factor with dual roles in transcription initiation and termination. Deregulation of MAZ expression is associated with the progression of pancreatic ductal adenocarcinoma (PDAC). However, the mechanism of action of MAZ in PDAC progression is largely unknown. Here, we present evidence that MAZ mRNA expression and protein levels are increased in human PDAC cell lines, tissue samples, a subcutaneous tumor xenograft in a nude mouse model, and spontaneous ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 76 publications
(79 reference statements)
0
39
0
Order By: Relevance
“…CYR61/CCN1 promotes growth and invasive phenotypes of PDAC cells via integrin-dependent noncanonical pathways. Moreover, our studies also showed that CYR61/CCN1 reprograms the epithelial-mesenchymal transition (EMT) and maintains cancer stemness/tumor-initiating properties that are associated with metastasis and drug resistance (18,21,22,(26)(27)(28)(29)(30). This provokes the hypothesis that PDAC cell-secreted CYR61/CCN1 signaling contributes to gemcitabine resistance.…”
Section: Introductionmentioning
confidence: 56%
See 4 more Smart Citations
“…CYR61/CCN1 promotes growth and invasive phenotypes of PDAC cells via integrin-dependent noncanonical pathways. Moreover, our studies also showed that CYR61/CCN1 reprograms the epithelial-mesenchymal transition (EMT) and maintains cancer stemness/tumor-initiating properties that are associated with metastasis and drug resistance (18,21,22,(26)(27)(28)(29)(30). This provokes the hypothesis that PDAC cell-secreted CYR61/CCN1 signaling contributes to gemcitabine resistance.…”
Section: Introductionmentioning
confidence: 56%
“…We and others have previously shown that CYR61/CCN1, which belongs to the CCN family of growth factors, acts as an oncoprotein in PDAC (21)(22)(23)(24)(25). CYR61/CCN1 promotes growth and invasive phenotypes of PDAC cells via integrin-dependent noncanonical pathways.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations